2015
DOI: 10.1021/acs.jpcc.5b07424
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Bonding and Electronic Properties of the Co Adatom and Dimer Interacting with Polyaromatic Hydrocarbons

Abstract: The density functional calculations presented here elucidate the nature of the interaction between the Co atom and dimer with a polyaromatic hydrocarbon (PAH). The results are analyzed in terms of structural, electronic and magnetic properties. The bonding character of the Co atom and dimer adsorbed on the PAH exhibits a strong covalent bonding, arising from a hybridization between the d orbitals of Co and the p z orbitals of the carbon atoms, which cause an in-plane distortion in the PAHs. A small charge tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 176 publications
(355 reference statements)
0
13
0
Order By: Relevance
“…This computational approach has been successful to describe the Pt/C and Co/C interactions. [16][17][18] The calculations were carried out using a polycyclic aromatic hydrocarbon (PAH) molecule as a representative example for modelling a real graphene material, since bonding to PAHs represents a model for binding to the π system relatively near defects in a real graphene material. Several PAH models were investigated in our previous work and the C 54 H 18 molecule was found to be a suitable model system.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…This computational approach has been successful to describe the Pt/C and Co/C interactions. [16][17][18] The calculations were carried out using a polycyclic aromatic hydrocarbon (PAH) molecule as a representative example for modelling a real graphene material, since bonding to PAHs represents a model for binding to the π system relatively near defects in a real graphene material. Several PAH models were investigated in our previous work and the C 54 H 18 molecule was found to be a suitable model system.…”
Section: Computational Detailsmentioning
confidence: 99%
“…13,14 Interfaces between transition metals (TM) and graphene have been investigated extensively by several theoretical and experimental techniques. [16][17][18][19][20][21][22] Müller et al investigated a single Pt atom, Pt dimers and trimers on highly oriented pyrolytic graphite using a scanning tunneling microscope (STM) in air. 21 The Pt particles were produced by evaporation of platinum onto the surface and the position of the Pt atoms were stable, without changes for many scans.…”
Section: Introductionmentioning
confidence: 99%
“…Often, clusters of transition metals (TM) supported on appropriate surfaces are the active catalysts, and the understanding of the cluster-support interaction is of great scientific and technological interest. Also, for many other purposes, the presence of adsorbed clusters can modify the electronic and magnetic properties of the substrate system 1 . There are some challenges regarding the adsorption of molecular species on supported metal clusters, related to the coupling of the clusters with the substrate [2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Another detection method less sensitive maybe based on the quenching of the magnetic moment of the Co2 clusters upon H2 adsorption. A recent DFT study showed that magnetic moment of two PAH-supported Co atoms is smaller than that of the end-on adsorbed dimer [27], therefore our calculations suggest that a sensor material based on Co2 rather than Co would be more sensitive. These rather technical aspects could become relevant for the design of functional conductive paramagnetic materials functionalised with Co2, which was recently shown to bind to graphene while preserving the magnetic properties of the cluster [46].…”
Section: Co2(h2)7mentioning
confidence: 62%
“…Magnetization measurements have shown considerable size-dependence of the magnetic moment in clusters with smaller clusters having higher magentic moments [26]. Therefore, the presence of high magnetic moments in small cobalt clusters such as Co2 and the possibility of funtionalising them to graphene sheets [27], makes them ideal for the development of novel materials for H-sensors or other megneto-electronic apllications in nanotechnology. There have been a few recent reports that have applied bimetallic [28] (e.g.…”
Section: Introductionmentioning
confidence: 99%